(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
New metal complexes of Mg(II), VO(II), Mn(II), Fe(III), Co(II), Ni(II), Cu(II) and Pd(II) with cyanex 301(L) i.e., bis(2,4,4-trimethylpentyl) dithiophosphinic acid were synthesized. The complexes have been characterized by elemental analysis, molar conductivity, molecular mass determination, magnetic measurements, infrared and electronic spectral studies. The prepared metal complexes have the compositions: 2. [MgL2].H2O, 3. [VOL2], 4. K[MnL3].H2O, 5. [FeL3], 6. K[CoL3].H2O, 7. K[NiL3], 8. K[CuL3] and 9. [PdL2]. The complexes 2, 3 and 9 are assumed to have tetrahedral, square pyramidal and square planar geometries, respectively but the complexes 4 - 8 are octahedral based on experimental data. From magnetic measurements the complexes 2 and 9 are found to be diamagnetic and others are paramagnetic. Measured molar conductance showed that the complexes 2, 3, 5 and 9 are non-electrolytes and rest are electrolytes. Besides, some complexes have shown good antibacterial and antifungal activities. Key words: Cyanex 301; Antibacterial; Antifungal; DMSO; Bis (2, 4, 4-trimethylpentyl) dithiophosphinic acid DOI: 10.3329/jbas.v34i2.6859 Journal of Bangladesh Academy of Sciences, Vol. 34, No. 2, 153-161, 2010